Reference Structure “pan / pani + imię” in Periodical Texts Published in Polish in Ukraine - Kravchuk, Alla (Respectus Philologicus, 2023)
The article’s author analyzes the function of the reference structure „pan / pani + imię” in the information texts of the Polish-language press in Ukraine in the first twenty years of the 21st century. The research shows that in the intentions of the speakers representing local Polish communities, the functions of these structures are always related to the expression of politeness. That is, the “scheme of title deprivation” characteristic of the general Polish language is not realized by adding the words “pan” or “pani” to the proper name in the narrative text. The members of the local Polish community, irrespective of their status, are the most numerous group of speakers using the analyzed structure. The reader, a member of the local community, perceives these forms as polite, and the external recipient may interpret them as violating the language etiquette (inappropriate, too familiar), especially if the hero of the statement is a Pole from Poland or a well-known person with high status.
Keywords: linguistic politeness; reference structure „pan / pani imię”; Polish in Ukraine; język polski w Ukrainie; language used in press